Management of Intraocular Pressure Elevation After CO2 Laser-Assisted Sclerectomy Surgery in Patients With Primary Open-Angle Glaucoma - Chen, Min; Gu, Yuxiang; Yang, Yumei; Zhang, Qi; Liu, Xin; Wang, Kaijun (Frontiers in Medicine, 2021)
Purpose: To report the safety and efficiency of CO2 laser assisted sclerectomy surgery (CLASS) in Chinese primary open angle glaucoma (POAG) patients, and the management of unexpected postoperative intraocular pressure (IOP) elevation. Methods: This was a prospective case series study. Totally, twenty-three eyes from 23 POAG patients who underwent CLASS were involved and followed up for 12 months. The primary outcomes included the changes in best-corrected visual acuity (BCVA), IOP and medications before and after CLASS. The secondary outcomes were success rate and postoperative laser interventions. Results: The mean age of the patient was 42.6 ± 16.0 years. There was no significant change in BCVA and visual field at baseline and 12 months after CLASS. The number of medications was significantly reduced after CLASS. The IOP was also significantly decreased and remained well controlled during the follow-up period, except for a transient elevation at 1 month postoperatively, due to the occurrence of peripheral anterior synechiae (PAS). Generally, 17 patients (73.9%) were treated with Nd:YAG laser synechiolysis to remove iris obstruction in the filtration site, and 7 patients (30.4%) underwent Nd:YAG laser goniopuncture to deal with scleral reservoir reduction. Only 1 patient (4.3%) received surgical repositioning due to iris incarceration. The complete success rate and total success rate at 12 months was 69.6% and 95.7%, respectively. Conclusions: CLASS was a safe and effective approach for Chinese POAG patients. PAS, iris incarceration and scleral reservoir reduction were common causes of unexpected postoperative IOP elevation. Individualized Nd:YAG laser intervention helps to improve the long-term outcomes after CLASS.